Occupational cold stress and rewarming alters skin temperature thresholds for manual dexterity decrements: An exploratory study - Christopher L. Chapman; Brandon M. Roberts; Erica A. Schafer; John W. Castellani; Karl E. Friedl; Adam W. Potter; David P. Looney (Physiological Reports)
Abstract The skin temperature thresholds at which precipitous reductions in dexterity occur in cold environments, and whether they are altered by rewarming, are not well defined. In three environmental conditions (20°C, 10°C, and 0°C air temperatures), 14 healthy adults (three females; age: 24 ± 6 years) completed five dexterity tests (Placing Test) over ~130 min of various light‐to‐moderate physical activities to simulate occupational work demands while minimally dressed. Brief passive rewarming (10 min in ~22°C air temperature) and a final dexterity test upon reentry to the environment was then performed. Dexterity was evaluated as the absolute (seconds) or percent change from an individual's best baseline performance. Prior to rewarming, segmented regression revealed thresholds for greater dexterity loss during progressive cold strain occurred at skin temperatures of ~22.9°C (fingers), ~24.9°C (hand), and ~22.4°C (forearm) (all p ≤ 0.002). After rewarming, this threshold shifted upwards to ~25.7°C for the fingers (p ≤ 0.007). The hand skin temperature threshold after rewarming was ~27.1°C (for absolute changes, p < 0.001), but one was not identified with percent change (p = 0.074). A forearm skin temperature threshold was not identified following rewarming (p ≥ 0.058). These findings indicate that, in non‐hypothermic conditions, skin temperature thresholds for dexterity loss during prolonged occupational cold stress may be modified with rewarming.